Performance of endovenous foam sclerotherapy in the USA for the treatment of venous disorders: ACP/SVM/AVF/SIR quality improvement guidelines. (March 2014) - Rathbun, S; Norris, A; Morrison, N; Gibson, K; Raymond-Martimbeau, P; Worthington-Kirsch, R; Hohenwalter, E; Lohr, J; McLafferty, R; Stoner, J
Objective: This report summarizes the findings of the consensus panel based on the results of the comprehensive questionnaire of US American College of Phlebology annual congress attendees and results of the systematic meta-analysis of the literature and provides quality improvement guidelines for the use of endovenous foam sclerotherapy (EFS) for the treatment of venous disorders, as well as identifies areas of needed research. Methods: Based on the above data, quality improvement guidelines were developed and reviewed by the ten US consensus panel members and approved by their respective societies. Results: EFS is effective for the treatment of truncal and tributary varicose veins, both as primary treatment and for treatment of recurrence. It may improve the signs and symptoms associated with varicose veins including pain and swelling. EFS is contraindicated in patients who have experienced an allergic reaction to previous treatment with foam or liquid sclerosant, and in patients with acute venous thrombosis events secondary to EFS. Conclusion: These guidelines for the use of EFS in the treatment of venous disorders provide an initial framework for the safe and efficacious use of this therapy, and the impetus to promote the evaluation of the questions remaining regarding the use of EFS through well-designed randomized and cohort studies.